Controls on the Formation of Lunar Multiring Basins. Issue 11 (21st November 2018) - Johnson, Brandon C.; Andrews‐Hanna, Jeffrey C.; Collins, Gareth S.; Freed, Andrew M.; Melosh, H. J.; Zuber, Maria T.
Abstract: Multiring basins dominate the crustal structure, tectonics, and stratigraphy of the Moon. Understanding how these basins form is crucial for understanding the evolution of ancient planetary crusts. To understand how preimpact thermal structure and crustal thickness affect the formation of multiring basins, we simulate the formation of lunar basins and their rings under a range of target and impactor conditions. We find that ring locations, spacing, and offsets are sensitive to lunar thermal gradient (strength of the lithosphere), temperature of the deep lunar mantle (strength of the asthenosphere), and preimpact crustal thickness. We also explore the effect of impactor size on the formation of basin rings and reproduce the observed transition from peak‐ring basins to multiring basins and reproduced many observed aspects of ring spacing and location. Our results are in broad agreement with the ring tectonic theory for the formation of basin rings and also suggest that ring tectonic theory applies to the rim scarp of smaller peak‐ring basins. Plain Language Summary: The largest impact craters on the Moon are multiring basins that exhibit three or more topographic rings. Great volumes of material were ejected and redistributed during the formation of these 1, 000‐km‐scale basins. Formation of these basins is the predominant process driving change of the lunar crust, the outermost layer of the Moon. Why large basins have multiple topographic rings and what they might tell us about the Moon remain poorly understood. Here we simulate the formation of these basins and their rings during an asteroid impact. We explore how thickness of the lunar crust, size of the impacting body, and interior temperature of the Moon affect the formation of basins and their rings. With well‐persevered multiring basins and an abundance of high‐quality gravity and topography data, the Moon is an ideal location to explore the formation of multiring basins. A better understanding of the formation of these basins will help us understand how similar basins may have affected the crusts of the Earth, Mars, Mercury, and Venus. Key Points: We simulate the formation of multiring basins exploring the effect of impactor size, target thermal structure, and crustal thickness Our simulations reproduce observed trends in ring spacing including the transition from peak‐ring to multiring structures Our results show that basin ring formation is quite sensitive to target thermal structure in general agreement with ring tectonic theory